PERLINDUNGAN HUKUM TERHADAP PELAPOR DALAM TINDAK PIDANA NARKOTIKA DI WILAYAH KEPOLISIAN RESOR KOTA PADANG - Amirahni Zahra Tripipo; Mexsasai Indra; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Revealing acts of criminal narcotics is , the apparatus not only obtain information from the actors , but the role and the community in helping officers enforcement of law to prevent and members antas abuse of narcotics . The importance of security guarantees and legal protection for whistleblowers so that the public does not feel afraid to report a crime that is associated with the offense of criminal narcotics , and with the assurance that real and Dapa t perceived by a complainant . This study aims to determine the implementation, obstacles and legal protection efforts against narcotics reporters at the Padang City Police.Type of research this can be classified into types of research sociological , because the study 's author Ian gsung conduct research into the location or field point that in carefully in order to provide an overview as complete and clear about the problem that is investigated . Research is conducted in satresnarkoba Police Padang while the population and the sample is a whole party that is associated with a problem that is investigated in the study of this source of data that is used primary data Data secondary and the data tertiary technique of collecting the data in the study is to interview and study of literature .From the results of the research there are three things staple that can be inferred . First , implementation of protection of law against the complainant in the investigation of acts of criminal abuse of narcotics in the Unit of Investigation Narcotics Police of Padang is the way : security protection , Concealing the identity of the complainant, the complainant did not present in court. Second , k endala constraints the implementation of legal protection against the complainant in a criminal offense narcotics Investigation Unit Narcotics Police of Padang, namely: Not existence of the institution the Agency in the area of West Sumatra as well , especially in the province in Padang , lack of participation of the public in reporting acts of criminal narcotics , Rapporteur still doubted the protection that would be given by officers of police , lack of budget operations and a member of the program of protection of witnesses . Third , efforts to overcome the obstacles in the legal protection against the reporting acts of criminal narcotics in Unit Detective Narcotics Police Resort Padang namely: Addition of Members and and optimization of budgetary funds, Doing dissemination to the public , provide an understanding to the public in order to not be afraid to report any acts of criminal narcotics to the apparatus of police , treat the complainant with a good and true , Giving rewards to whistleblowers . The author's suggestion is that the public is expected to participate in reporting criminal acts of narcotics, and not be afraid to report them to law enforcement officials so that the future of the nation is safe from drugs.Keywords: Legal Protection - Reporting - Narcotics